2015
DOI: 10.1111/ajsp.12104
|View full text |Cite
|
Sign up to set email alerts
|

The influence of self-efficacy, subjective norms, and risk perception on behavioral intentions related to the H1N1 flu pandemic: A comparison between Korea and the US

Abstract: This study examined the extent to which individualism-collectivism moderates the relative effects of agency control beliefs (i.e., self-efficacy), social norms (i.e., subjective norms), and risk perception (perceived vulnerability and perceived severity) on behavioral intention to engage in self-protection behavior in the context of the H1N1 flu pandemic. Using multistage stratified sampling, the present study sampled people from the US (n = 399) and Korea (n = 500), two countries that have been found to be pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
79
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(89 citation statements)
references
References 69 publications
8
79
1
1
Order By: Relevance
“…Secondly, the influence of the social norm on the values associated with entrepreneurship (H2) has also been confirmed, both in the case of Spain and in Poland, as suggested by other authors in this and other fields [118,120]. However, this influence is not very high, and is somewhat higher in the case of Poland.…”
Section: Discussion and Theoretical Implicationssupporting
confidence: 66%
See 3 more Smart Citations
“…Secondly, the influence of the social norm on the values associated with entrepreneurship (H2) has also been confirmed, both in the case of Spain and in Poland, as suggested by other authors in this and other fields [118,120]. However, this influence is not very high, and is somewhat higher in the case of Poland.…”
Section: Discussion and Theoretical Implicationssupporting
confidence: 66%
“…It is a proven fact that the social norm influences values [118]. It is due to the influence exercised by the social norm that individuals adopt certain values when they perceive that these values and associated behaviors are expected and approved by significant and influential agents [119,120]. Additionally, in a generational context, it is assumed that young people share values and are easily influenced by other subjects, due to the pressure of conformity [121].…”
Section: Model and Hypothesismentioning
confidence: 99%
See 2 more Smart Citations
“…Self-efficacy was found as a predictor of the intention and practice of health behavior and risk perception (Joffe, 2003;Seyde, Taal, & Wiegman, 1990). A recent study of Cho and Lee (2015), which investigated the influence of self-efficacy and risk perception on behavioral intentions related to the A/H1N1 flu pandemic, showed that culture affected selfefficacy and risk perception. According to the authors, the way in which people perceive and respond to risks varied across nationalities and cultures.…”
Section: Psychological Variables and Infectious Diseasesmentioning
confidence: 99%